(untitled) (World Bulletin of Social Sciences, 2024)
This article is aimed at research and development of a unified digital transport and logistics intelligent platform based on the infrastructure of the national operator. Given the rapid development of the transport and logistics sector, the creation of this platform is an important strategic initiative.